MEDIA DIGITAL INTERAKTIF DALAM PEMBELAJARAN MUSIK UNTUK ANAK USIA SEKOLAH DASAR: TINJAUAN LITERATUR - Rizqia Rahmah Fauziyah; Resa Respati; Pidi Mohamad Setiadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article aims to examine the utilization of interactive digital media in musiclearning for elementary school children through a literature review approach. Themethod involves systematic analysis of relevant studies published between 2010and 2024, retrieved from academic databases such as Google Scholar,ScienceDirect, and the National Library of Indonesia. Interactive digital media,including educational music applications, virtual instruments, and web-basedplatforms, are found to be effective in enhancing students’ motivation, musicalskills, and creativity through multisensory and interactive engagement. The resultsindicate that these media contribute positively to children’s cognitive, motor, social,and emotional development, despite facing challenges such as limitedtechnological infrastructure, low teacher competence in technology, andmisalignment between content and the national curriculum or local cultural context.Therefore, strategies like teacher training, development of localized content, andimplementation of blended learning are essential for successful media integration.This study contributes to the development of effective, relevant, and engaginginstructional media for music education at the elementary level.